The Effect of Brand Image, Brand Trust, and Promotion on Consumer Loyalty - Kuwat Riyanto; Yulia Andiyani (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
This study aims to determine the effect of brand image, brand trust, and promotion on consumer loyalty Pocari Sweat in Cikarang. This study uses the brand image variable which is measured using 3 dimensions, namely: strength, uniqueness, and preference. The brand trust variable is measured using 2 measurement dimensions, namely: reliability and purpose. Promotional variables were measured using 5 measurement dimensions, namely: advertising, sales promotion, personal selling, public relations, and direct marketing. Consumer loyalty variable is measured using 5 measurement dimensions, namely: trust, emotional commitment, switching costs, word of mouth, and cooperation. This research is a quantitative study with a sampling technique using the non probability sampling method and multiple linear regression analysis. The results of the study partially there is no significant effect between brand image on consumer loyalty, partially there is a significant influence between brand trust and promotion on consumer loyalty.